Murder is easy - Christie, Agatha (HarperCollins London, 2002)
Luke Fitzwilliam could not believe Miss Pinkerton's wild allegation that a multiple murderer was at work in the quiet English village of Wychwood. But when she is killed, followed by Dr Humbleby, he begins to change his mind